Governance functions in subak empowerment: a documentary case study - Ni Luh Ayu Gustina Dewi; Anak Agung Ngurah Eddy Supriyadinata Gorda (Lentera Negeri, 2026)
This study examines village governance functions in Subak empowerment through a documentary qualitative case study of Mengwitani, Bali. The unit of analysis is each village program or decision concerning irrigation infrastructure, institutional participation, access to agricultural support, cultural continuity, and operational risk. The purposively selected corpus comprises the 2025 Mengwitani Village Profile, relevant legal instruments, and issue-based records from preliminary institutional notes. The available materials do not contain a complete interview register, so participant counts, saturation, and interview-based generalization are not claimed. Data were analyzed through directed qualitative content analysis using four operational categories: regulator, dynamizer, facilitator, and catalyst. Evidence was coded manually in a source matrix, compared across source types, and checked through an audit trail, negative-case review, and explicit separation of findings from recommendations. Facilitation is the most clearly documented function, reflected in farm-road improvement, irrigation retaining-wall reinforcement, granary rehabilitation, customary-facility support, and access to regency input programs. Representative participation appears through Pekaseh proposals, while structured training, a specific village regulation on land conversion, and a formal collaborative platform remain incomplete. The analysis identifies an emergent configuration that is infrastructure-centered, proposal-mediated, culturally embedded, and risk-conscious. This configuration is descriptive and context-specific, not a causal or generalizable model. Validation requires completed community interviews, longitudinal land-use data, and outcome indicators.